Modeling seismic risk and economic loss for urban sustainability: insights from a Gulf city - Abdullah Ansari; Issa El-Hussain; Yousuf Al-Shijbi; Ayed E. Alluqmani; Hajar Al-Qayoudhi; Yewuhalashet Fissha; Shima Albalushi; Badee Alshameri (Modeling Earth Systems and Environment, 2026)
This study delivers the first comprehensive microzonation-based seismic risk assessment for the Al-Seeb region in Muscat, Oman. It integrates geotechnical, structural, environmental, and socio-economic vulnerability factors using a Geographical Information System (GIS) based multi-criteria framework. The Analytic Hierarchy Process (AHP) was employed to systematically weight and integrate these indicators, ensuring an objective evaluation of their relative influence on overall seismic vulnerability. Moving beyond traditional methods, it translates microzonation data into spatially distributed Average Annual Loss (AAL) zones and estimates economic impacts through Loss Exceedance Curves (LEC) and Probable Maximum Loss (PML). By coupling detailed hazard zonation with building typologies and infrastructure exposure, the study develops an asset-level risk profile, revealing sharp spatial variations in seismic risk driven by site conditions and construction quality. The results serve as a vital planning tool for civil authorities, aligning with Oman Vision 2040 and United Nations Sustainable Development Goal (UN SDG) 11. The approach offers a scalable model for rapidly urbanizing Gulf cities such as Doha, Riyadh, Dubai, and Kuwait, providing a data-informed foundation for enhancing infrastructure resilience and strengthening disaster risk management strategies.

Application of multiple machine learning algorithms for intelligent prediction of the strength of fine-grained natural soils - Muhammad Shahroz Khalid; Zia ur Rehman; Badee Alshameri; Zain Maqsood; Fazal Hussain; Muhammad Irslan Khalid; Syed Jamal Arbi; Abbas Haider (Arabian Journal of Geosciences, 2025)

A novel numerical approach for the assessment of the seepage failure, predictive modelling of seepage through non-homogenous earth-fill dams resting on pervious foundations using artificial neural networks - Muhammad Zeeshan Khursheed; Badee Alshameri; Waqas Hassan; Lokmane Abdeldjouad (Modeling Earth Systems and Environment, 2025)

Geospatial intelligence in geotechnical engineering: a comprehensive investigation into SPT-N, soil types, and undrained shear strength for enhanced site characterization - Waqas Hassan; Muhammad Qasim; Badee Alshameri; Arfan Shahzad; Muhammad Hamza Khalid; Sana Ullah Qamar (Bulletin of Engineering Geology and the Environment, 2024)

Comparison of Seepage Evaluation Methods for Earth-Filled Embankments: A Case Study of Sukian Dyke, Mangla Dam - Muhammad Hamza Khalid; Tanzeela Yasmin; Badee Alshameri; Syed Muhammad Jamil; Waqas Hassan (Modeling Earth Systems and Environment, 2024)

Investigate and Analysis the Efficiency of Existing Recommendations of Near-Field Effect and Boundary Conditions on Bender Element Technique - Badee Alshameri (Pure and Applied Geophysics, 2023)

PET waste management in Pakistan through use of PET shreds as additive in backfill soil - Fawad Sheikh; Badee Alshameri; Zain Maqsood; Abbas Haider; Jawad Hassan (Environmental Monitoring and Assessment, 2023)

Normalization of geotechnical sustainability assessment tool (Geo-SAT) using multiple criteria decision analysis for dams - Kainat Batool; Badee Alshameri; Faisal Raza; Abbas Haider; Majid Ali (Environment, Development and Sustainability, 2023)

Statistical interpolation and spatial mapping of geotechnical soil parameters of District Sargodha, Pakistan - Waqas Hassan; Muhammad Fazal Raza; Badee Alshameri; Arfan Shahzad; Muhammad Hamza Khalid; Muhammad Naqeeb Nawaz (Bulletin of Engineering Geology and the Environment, 2023)

Experimental study on shear strength behavior and numerical study on geosynthetic-reinforced cohesive soil slope - Waqas Hassan; Badee Alshameri; Muhammad Naqeeb Nawaz; Sana Ullah Qamar (Innovative Infrastructure Solutions, 2022)

Comparative study of various interpretative methods of the pile load test - Ahrar Mahmood; Badee Alshameri; Muhammad Hamza Khalid; S. Muhammad Jamil (Innovative Infrastructure Solutions, 2022)

Engineering aspect of sustainability assessment for geotechnical projects - Faisal Raza; Badee Alshameri; S. Muhammad Jamil (Environment, Development and Sustainability, 2021)

Assessment of triple bottom line of sustainability for geotechnical projects - Faisal Raza; Badee Alshameri; S. Muhammad Jamil (Environment, Development and Sustainability, 2021)

Comprehensive Correlations Between the Geotechnical and Seismic Data Conducted via Bender Element - Badee Alshameri; Aziman Madun (Geotechnical and Geological Engineering, 2019)